NHS Nightingale North West: A Medical Student on the Front Lines - Holt, Lewis (International Journal of Medical Students, 2020)
Seemingly overnight, on the 12th of March 2020, healthcare systems the world over changed as the World Health Organisation deemed COVID-19 a worldwide pandemic. I was moved directly into the fourth year of my medical studies without examination, and applied to work in one of the few field hospitals set up across the United Kingdom, designed to handle to worst case scenario of COVID-19. Here I tended to the most basic needs of patients as a care support worker and witness first hand the relentlessness of this awful disease. Being able to help and work in a role I was not familiar with has given me great insight into the needs of patient’s whether they are going home or in their final days of life. As the pandemic cools down and the incidence curve flattens, we have all been put on standby, hopefully not to be required again.